2006
DOI: 10.1051/0004-6361:20064953
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic electron acceleration in the force-free corona with anomalous resistivity

Abstract: Aims. We numerically explore electron acceleration and coronal heating by dissipative electric fields. Methods. Electrons are traced in linear force-free magnetic fields extrapolated from SOHO/MDI magnetograms, endowed with anomalous resistivity (η) in localized dissipation regions where the magnetic twist ∇ ×b exceeds a given threshold. Associated with η > 0 is a parallel electric field E = ηj which can accelerate runaway electrons. In order to gain observational predictions we inject electrons inside the dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Radio The radio emission can be observed during eruptive events such as flares, CMEs or filament eruptions, and it has been often suggested that the radio emission in the high corona occurs at the interface between closed and open magnetic field regions (Klassen et al, 1999;Bentley et al, 2000;Paesold et al, 2001;Aurass et al, 2003Aurass et al, , 2005Aurass et al, , 2011Grechnev et al, 2006;Arzner and Vlahos, 2006;Hofmann and Ruždjak, 2007;Wen, Wang, and Zhang, 2007;Klein et al, 2008;Chen et al, 2011;Tun, Gary, and Georgoulis, 2011;Del Zanna et al, 2011;Iwai et al, 2012;Hao et al, 2012). The gyroemission is also used to determine the strength of the magnetic field in the corona (Pallavicini, Sakurai, and Vaiana, 1981;Schmahl et al, 1982;Hildebrandt, Seehafer, and Krueger, 1984;Brosius et al, 1997Brosius et al, , 2002Lee et al, 1998Lee et al, , 1999Grebinskij et al, 2000;Ryabov et al, 2005;Bogod, Stupishin, and Yasnov, 2012).…”
Section: Optical Wavelengthsmentioning
confidence: 99%
“…Radio The radio emission can be observed during eruptive events such as flares, CMEs or filament eruptions, and it has been often suggested that the radio emission in the high corona occurs at the interface between closed and open magnetic field regions (Klassen et al, 1999;Bentley et al, 2000;Paesold et al, 2001;Aurass et al, 2003Aurass et al, , 2005Aurass et al, , 2011Grechnev et al, 2006;Arzner and Vlahos, 2006;Hofmann and Ruždjak, 2007;Wen, Wang, and Zhang, 2007;Klein et al, 2008;Chen et al, 2011;Tun, Gary, and Georgoulis, 2011;Del Zanna et al, 2011;Iwai et al, 2012;Hao et al, 2012). The gyroemission is also used to determine the strength of the magnetic field in the corona (Pallavicini, Sakurai, and Vaiana, 1981;Schmahl et al, 1982;Hildebrandt, Seehafer, and Krueger, 1984;Brosius et al, 1997Brosius et al, , 2002Lee et al, 1998Lee et al, , 1999Grebinskij et al, 2000;Ryabov et al, 2005;Bogod, Stupishin, and Yasnov, 2012).…”
Section: Optical Wavelengthsmentioning
confidence: 99%
“…The diffusive part of the electric field (ηj) included in the induction equation is responsible for both changing the magnetic field topology and for transforming magnetic energy into Joule dissipation in the MHD picture. In the Sun the diffusive electric field component parallel to the magnetic field is responsible for particle acceleration (Arzner and Vlahos, 2006). It is therefore of particular interest to see how this field evolves with the boundary displacement, and to find out where it concentrates and how large values it reaches.…”
Section: Time Evolution Of the Diffusive Electric Fieldmentioning
confidence: 99%
“…Simulations of this kind revealed how particles are accelerated in 3D magnetic nullpoints (Dalla and Browning 2006), in 2D X-points with a single X-line (Hannah and Fletcher 2006), in force-free fields with anomalous resistivity (Arzner and Vlahos 2006), in strong turbulence regions , in particular for 3 He and 4 He ions (Liu et al 2006e), in spatially intermittent turbulence regions (Decamp and Malara 2006), in stochastic current sheets of stressed fields (Turkmani et al 2006), in 3D Harris reconnecting current sheets where particles follow chaotic, regular, and mirror-type regular orbits (Gontikakis et al 2006), or in fan 3D reconnection geometries (Litvinenko 2006). The highest energies of accelerated, gamma-ray producing particles reported this year went up to >200 MeV, produced by neutral pion decay (Kuznetsov et al 2006).…”
Section: Particle Accelerationmentioning
confidence: 99%